2018 IEEE Power &Amp; Energy Society General Meeting (PESGM) 2018
DOI: 10.1109/pesgm.2018.8585977
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methods for Determining Inception and Recovery Points of Voltage Variation Events

Abstract: Voltage sags and swells occur often in power systems; however determining the duration of these events is not straightforward. Seven methods for estimating the inception and recovery points (and consequently, the duration) of voltage sags and swells are surveyed: threshold rms voltage, waveform envelope, discrete wavelet transform, missing voltage, dq transformation, numerical matrix, and peak detector. Each method has its own strengths and weaknesses; however, no one method works on all conditions. An algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…The lowest time latency for the traditional method is obtained through short sliding windows (half-cycle) and high update rate (rms values computed for each new voltage sample). However, even this approach has been shown to introduce a relatively high time latency [22]. Additionally, the estimated event duration depends on the instants at which the rms values are computed.…”
Section: Motivation -The Traditional Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The lowest time latency for the traditional method is obtained through short sliding windows (half-cycle) and high update rate (rms values computed for each new voltage sample). However, even this approach has been shown to introduce a relatively high time latency [22]. Additionally, the estimated event duration depends on the instants at which the rms values are computed.…”
Section: Motivation -The Traditional Methodsmentioning
confidence: 99%
“…A previous survey indicated that the discrete wavelet transform (DWT) presents the best performance among the methods for determining the inception and recovery points of a voltage sag [22]. Fig.…”
Section: E Comparison To the Discrete Wavelet Transform Methodsmentioning
confidence: 99%
See 3 more Smart Citations